Thermoreversible Siloxane Networks: Soft Biomaterials with Widely Tunable Viscoelasticity. (15th July 2019) - Meng, Yuan; Xu, Weijing; Newman, Maureen R.; Benoit, Danielle S. W.; Anthamatten, Mitchell
Abstract: Polysiloxane elastomers represent a widely utilized soft material with excellent rubber‐like elasticity, biocompatibility, and biodurability; however, there is a lack of an effective and straightforward approach to manipulate the material's viscoelastic response. A facile hydrosilylation reaction is employed to integrate ureidopyrimidinone hydrogen‐bonding side‐groups into linear and crosslinked siloxane polymers to achieve biocompatible soft materials with a highly tunable viscoelastic relaxation timescale. Stacking of H‐bonded moieties is avoided in the designed macromolecular architectures with tight, side‐groups substituents. The obtained siloxane network features the presence of both covalent crosslinks and truly thermoreversible crosslinks, and can be formulated across a broad material design space including elastic solids, recoverable viscoelastic solids, and viscous liquids. The elastomers exhibit unique temperature‐dependent shape‐memory capability and show good cytocompatibility. Importantly, a deformed material's shape‐recovery occurs regardless of external triggering, and through manipulation of network formulations, the shape‐recovery timescale can be easily tuned from seconds to days, opening new possibilities for biomedical, healthcare, and soft material applications. Abstract : A novel polysiloxane formulation with strong ureidopyrimidone hydrogen bonding side‐groups extends stress relaxation timescales by orders of magnitude—from seconds to days. Once crosslinked, the obtained siloxane networks feature large viscoelastic shape memory regardless of ambient temperature, as well as biocompatibility, which enables biomedical applications.